2010
DOI: 10.1111/j.1439-0388.2009.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening 52 single nucleotide polymorphisms for extreme value of glycolytic potential and drip loss in pigs

Abstract: Summary Low heritability of meat quality traits and the lack of their systematic registration in breeding programs have encouraged the search for single nucleotide polymorphisms (SNPs) located within genes coding the proteins involved in muscle and fat metabolism. In this report, a panel of 52 SNPs was used to find which alleles and genotypes are more/less frequent in groups of pigs differentiated by extreme value of glycolytic potential (GP) and drip loss (DL). The analysis was carried out in 52 fatteners (ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The average GP values reported by these authors for each of the three possible genotypes were similar to those obtained in this study. Moreover, Kamiński et al [34] reported the effect of the DECR1 on GP, glycogen metabolism, and meat quality and the reported values of these parameters were similar to those obtained in the present study. DECR1 is a nuclear gene encoded by a mitochondrial enzyme that participates in the fatty acid beta-oxidation pathway.…”
Section: Meat Qualitysupporting
confidence: 79%
See 1 more Smart Citation
“…The average GP values reported by these authors for each of the three possible genotypes were similar to those obtained in this study. Moreover, Kamiński et al [34] reported the effect of the DECR1 on GP, glycogen metabolism, and meat quality and the reported values of these parameters were similar to those obtained in the present study. DECR1 is a nuclear gene encoded by a mitochondrial enzyme that participates in the fatty acid beta-oxidation pathway.…”
Section: Meat Qualitysupporting
confidence: 79%
“…Despite that the pigs originated from herds belonging to the program of elimination of disadvantageous genes' influence on meat quality (RYR1 T and RN -), approximately 10 % of the 75 meat samples were classified as PSE and a similar percentage was found for acid meat. However, PSE meat and meat with low pH levels have been observed in races lacking these two genes [17,19,34,35], which may have been due to stress conditions of preslaughter trade, slaughter, and feeding [19,36]. The electrical low voltage stunning may contribute to the occurrence of PSE meat [37,38].…”
Section: Meat Qualitymentioning
confidence: 99%
“…Other genes for which associations with pH Downloaded by [McGill University] at 09:24 13 June 2016 have been reported include myogenin ), PKM2 , and troponin I (Yang et al 2010). PKM2 and CYP21 are associated with drip loss and DECR1 has been associated with glycolytic potential (Kaminski et al 2010). …”
Section: Polymorphisms Associated With Water-holding Capacity and Colormentioning
confidence: 95%
“…Stress reactions before the slaughter procedure influences ante-and post-mortem muscle metabolism. Its polymorphism discovered by bioinformatics approach is localized in the putative intron splicing site suggesting possible influence on messenger RNA (mRNA) stability and CYP21 biosynthesis efficiency (Kami nski et al 2010). In pigs, high preslaughter stress led to increasing plasma cortisol levels.…”
Section: Introductionmentioning
confidence: 99%